2020
DOI: 10.1111/are.15029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary four different woody forages on gut microbiota of Nile tilapia ( Oreochromis niloticus )

Abstract: The present study investigated for the first time the gut bacterial responses of Nile tilapia (Oreochromis niloticus) to four different woody forages (Moringa oleifera, fermented M. oleifera, Folium mori and fermented F. mori meals) by high‐throughput Illumina sequencing. Forty‐eight bacterial phyla and a very different bacterial community consisted of Paeniclostridium, Clostridium, Mycobacterium, Synechococcus, Cetobacterium, Trachydiscus and Romboutsia were detected in this study. Interestingly, it was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The Protebacteria phylum was identified as the most prevalent member (>96% of the total bacteria) in both GI cultures, where the unclassified Enterobacteriaceae , Desulfovibrio , and Klebsiella taxa were the two most abundant genera with higher proportions (Figures and S11). The distributions of the major phyla ( Firmicutes , Bacteroidetes , and Proteobacteria ) are consistent with previous gut studies of fish and other aquatic animals, indicating constant core gut bacteria across a broader range of species. , Enterobacteriaceae was also reported as the common amylolytic and lipolytic bacteria in GI tract, while Klebsiella and Desulfovibrio were the representative genera exhibiting high abundance in freshwater fish gut. , Fungal communities remained stable throughout the enrichment process. The most abundant phylum was Ascomycota in all samples (>62.8%, Figure S10), which was also found as a typical heterotrophic fungi tax in fish gut from previous studies. , Aureobasidium , Fusarium , and Aspergillus were the most prominent group in the Ascomycota phylum at the genus level (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Protebacteria phylum was identified as the most prevalent member (>96% of the total bacteria) in both GI cultures, where the unclassified Enterobacteriaceae , Desulfovibrio , and Klebsiella taxa were the two most abundant genera with higher proportions (Figures and S11). The distributions of the major phyla ( Firmicutes , Bacteroidetes , and Proteobacteria ) are consistent with previous gut studies of fish and other aquatic animals, indicating constant core gut bacteria across a broader range of species. , Enterobacteriaceae was also reported as the common amylolytic and lipolytic bacteria in GI tract, while Klebsiella and Desulfovibrio were the representative genera exhibiting high abundance in freshwater fish gut. , Fungal communities remained stable throughout the enrichment process. The most abundant phylum was Ascomycota in all samples (>62.8%, Figure S10), which was also found as a typical heterotrophic fungi tax in fish gut from previous studies. , Aureobasidium , Fusarium , and Aspergillus were the most prominent group in the Ascomycota phylum at the genus level (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…29,69−71 Enterobacteriaceae was also reported as the common amylolytic and lipolytic bacteria in GI tract, 70 while Klebsiella and Desulfovibrio were the representative genera exhibiting high abundance in freshwater fish gut. 72,73 Fungal communities remained stable throughout the enrichment process. The most abundant phylum was Ascomycota in all samples (>62.8%, Figure S10), which was also found as a typical heterotrophic fungi tax in fish gut from previous studies.…”
Section: Gi Microbiota Characterization and Identification Of Degrada...mentioning
confidence: 99%
“…Mycobacterium, which belongs to Actinobacteria, is a pathogen of fsh and human coinfection [84][85][86]. Zhang et al [87] reported that the content of Mycobacterium in the intestines of Nile tilapia (Oreochromis niloticus) is abundant when fed with diferent woody forages. According to the correlation analysis of this experiment, it has been proven that a high-carbohydrate diet promotes Mycobacterium booming.…”
Section: Correlation Analysis Between Intestinal Microbiota and Metab...mentioning
confidence: 99%
“…After each sh was cut in an arc along the anus in an upward direction with dissecting scissors, its intestine was separated and divided into fore-, mid-and hind-intestinal segments with dissecting scissors (Wu et al 2020). Then the mucosa (including intestinal contents) of each intestinal segment was individually collected with sterile dissecting scissors, and nally, 0.5 g of the mucosa was gently scraped into a centrifuge tube (Zhang et al 2021). Then, 0.5 mL of each of the three seawater samples was diluted into 4.5 mL of sterile seawater.…”
Section: Fungal Isolation Of Sh Intestines and Seawatermentioning
confidence: 99%